IS THE CHANGING RAINFALL PATTERNS OF KANO STATE AND ITS ADVERSE IMPACTS AN INDICATION OF CLIMATE CHANGE? - Abaje, I.B.; Ndabula, C.; Garba, A.H. (European Scientific Journal, ESJ, 2014)
Annual and monthly rainfall data for Kano from the period 1911 to 2010 (100 years) were used in this study to determine the changing patterns of rainfall and its adverse impacts on transport infrastructures. The Relative Seasonality Index of the rainfall series revealed that the rainfall is in 3 months or less. In order to identify trends, the rainfall series was divided into 10-year non-overlapping and 30-year overlapping sub-periods and the Cramer’s test was then used to compare the means of the sub-periods with the mean of the whole record period. The results of the 10-year nonoverlapping sub-period analysis revealed a recent increase in the annual rainfall series in the last two sub-periods (1991-2000 and 2001-2010). The results of the 30-year overlapping sub-periods analysis also revealed that the recent sub-period, 1981-2010, was significantly wetter than the long-term conditions. Findings revealed that the increase in annual rainfall amount in recent years is as a result of the increased in June, July and August rainfalls. This may be responsible for the frequent occurrences of floods in the months of July and August which is an indication of climate change. The 10-year running mean shows that the increasing yield of the annual rainfall started from the mid 1990s to the end of the study period. The major implication of this increased in amount and intensity of rainfall on transport infrastructures is that models built on the perceived decreasing rainfall, such as drainages, bridges, etc, have to be reviewed. It is recommended that planning and designing of transport infrastructures should take into account the recent increasing nature of rainfall.